Pediatric bipolar disorder versus developmental trauma and holistic assessment and care: the contribution of Dr. Ed Levin - Parry, Peter I. (Frontiers in Psychiatry, 2025)
This perspective article presents the work of Dr. Edmund (Ed) C Levin (1931-2022), child and adolescent psychiatrist in Berkeley, California. Levin drew from over half a century of continuity of clinical practice with his patients and knowledge of developmental psychopathology. He was witness to a paradigm shift in American psychiatry from what Eisenberg termed a ‘brainless’ to a ‘mindless’ approach in research and clinical practice. He was motivated by concern for medical ethical treatment guided by awareness of the patient’s individual biopsychosocial contributing factors to their predicament and symptoms. He addressed the pediatric bipolar disorder era by championing a recognition of the long-term effects of childhood maltreatment and developmental trauma across the lifespan. His work in both child and youth residential and geriatric residential units exemplified this.